Policing and Community Policing System in India for Controlling Crimes: Revitalizing Policing through Community Engagement (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Policing in any country under any system of governance and during any period of time has always been a responsibility of the ruler. The State emerged to ensure security and peace to the individual. In order to realize these objectives, the State created an administrative system of which the police is an important component. The Oxford dictionary defines police as an official organization whose job is to make people obey the law and to prevent and solve crime.1 With the social, political and economic changes in the society, the duties and functions of the police also changed. There was a time when the police functioned as a coercive force to catch criminals and prosecute them for their misdeeds. It was not assigned the tasks which would bring it closer to the people in a positive manner. Many times the obligations imposed by the law on various State authorities turn to be rights and privileges of the people. In the matters of prevention and investigation of crime the police cannot achieve desired results without the assistance and help of the people. The police cannot be omnipresent and therefore members of the public are expected to function as its ears and eyes. In order to help Police and for the security of People the concept of Community Policing was emerged. The Community policing has far-reaching implications. The expanded outlook on crime control and prevention, the new emphasis on making community members active participants in the process of problem solving, and the patrol officers’ pivotal role in community policing require profound changes within the police organization. Reinvigorating communities is essential if we are to deter crime and create more vital neighborhoods.